2015
DOI: 10.1142/s0129183115500291
|View full text |Cite
|
Sign up to set email alerts
|

The role of fanatics in consensus formation

Abstract: A model of opinion dynamics with two types of agents as social actors are presented, using the Ising thermodynamic model as the dynamics template. The agents are considered as opportunists which live at sites and interact with the neighbors, or fanatics/missionaries which move from site to site randomly in persuasion of converting agents of opposite opinion with the help of opportunists. Here, the moving agents act as an external influence on the opportunists to convert them to the opposite opinion. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the real world interpersonal communication (like in artificial society), an individual may confront other people with diverse opinions. We use random-neighbour interaction rule to model such interaction among agents dependent on spatial location; wherein each agent randomly moves to a cell site with equal probability (Liu and Wang 2013;Gündüç 2015).…”
Section: Model Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the real world interpersonal communication (like in artificial society), an individual may confront other people with diverse opinions. We use random-neighbour interaction rule to model such interaction among agents dependent on spatial location; wherein each agent randomly moves to a cell site with equal probability (Liu and Wang 2013;Gündüç 2015).…”
Section: Model Proceduresmentioning
confidence: 99%
“…We observed that an increment in the ZB leads to opinion shift towards majority opinion (B) even with the ZA that are well beyond critical population except in a few runs due to perturbations. Such an increase in supporters of majority opinion acts as a resistance (Gündüç 2015) for the opinion shift towards the ideology A (Fig. 14).…”
Section: Without External Influence and Zealots Of Old Ideologymentioning
confidence: 99%
“…The united group may persuade the individuals living at the neighboring sites according to both the number and their persuasion ability. Also in other paper [18], we studied the role of fanatics in consensus formation. A model of opinion dynamics with two types of agents as social actors are presented, using the Ising thermodynamic model as the dynamics template.…”
Section: Introductionmentioning
confidence: 99%